(untitled) (Orfeu, 2020)
The present article is a step towards organizing the corpus for extended violin techniques didactic resources, by the means of an exploratory bibliographic investigation. It departs from a proposed categorization of extended techniques, which enables studying them in more detail, and has been focused in the category defined as “sound production techniques specific to the violin”. The study has found that there is a considerable amount of textual and musical works. Among textual works, despite all of them having some relevance, not all of them are decidedly didactic; among the musical ones, the sample has brought a small number of etudes and pieces that in fact explore this category of techniques.